Hubungan Indeks Massa Tubuh (IMT) Dengan Resiko Preeklamsia Pada Ibu Hamil Trimester III - Nadiro, Aliyatul Himmah; Subiastutik, Eni; Sasmito, Lulut (Jember Maternal and Child Health Journal, 2024)
10-12% of pregnancies are accompanied by complications. Preeclampsia is characterized by blood pressure ?140/90 mmHg. The prevalence of preeclampsia in Indonesia is 128,273 cases/year, East Java province 14,126 cases, and Jember Regency 936 cases. BMI is one of the factors that influence preeclampsia. The purpose of this study was to determine the relationship between Body Mass Index (BMI) and the risk of preeclampsia. The study population of 73 pregnant women in the third trimester, with a Random Sampling technique of 62 respondents. Data collection using observation sheets. Data analysis with Pearson Chi-Square and Odds Ratio tests. The results obtained 33.87% of respondents had overweight BMI, 25.81% had normal BMI, 16.13% had underweight BMI, and 24.19% had obese BMI. The proportion of preeclampsia incidents was 53.23% and no preeclampsia 44.67%. There is a relationship between Body Mass Index and the risk of preeclampsia with ?-value = 0.002 <? 0.05. Excessive/high BMI has a 12 times higher risk of preeclampsia compared to normal BMI. The higher the BMI value, the higher the risk of preeclampsia. Balanced food intake, and monitoring of BMI during pregnancy adjusted to BMI in early pregnancy and blood pressure measurement need to be considered during ANC visits to determine the risk of preeclampsia.